Contribution of permafrost soils to the global carbon budget - Schaphoff, S.; Heyder, U.; Ostberg, S.; Gerten, D.; Heinke, J.; Lucht, W. (IOP Publishing, 2013)
Climate warming affects permafrost soil carbon pools in two opposing ways: enhanced vegetation growth leads to higher carbon inputs to the soil, whereas permafrost melting accelerates decomposition and hence carbon release. Here, we study the spatial and temporal dynamics of these two processes under scenarios of climate change and evaluate their influence on the carbon balance of the permafrost zone. We use the dynamic global vegetation model LPJmL, which simulates plant physiological and ecological processes and includes a newly developed discrete layer energy balance permafrost module and a vertical carbon distribution within the soil layer. The model is able to reproduce the interactions between vegetation and soil carbon dynamics as well as to simulate dynamic permafrost changes resulting from changes in the climate. We find that vegetation responds more rapidly to warming of the permafrost zone than soil carbon pools due to long time lags in permafrost thawing, and that the initial simulated net uptake of carbon may continue for some decades of warming. However, once the turning point is reached, if carbon release exceeds uptake, carbon is lost irreversibly from the system and cannot be compensated for by increasing vegetation carbon input. Our analysis highlights the importance of including dynamic vegetation and long-term responses into analyses of permafrost zone carbon budgets.